Collecting the dead: art, antique and 'aura' in personal collections of murderabilia. (2nd July 2020) - Denham, Jack
ABSTRACT: Murderabilia (murder-memorabilia) has enjoyed increasing tabloid attention over the past two-decades. It follows a sustained appetite for the consumption or more 'mainstream' forms of crime and death-based culture, yet has not been explored in a dedicated academic study. Building on work in this journal that has considered dead criminals, the consumption of corpses more generally, or the way that we 'play' with death in popular culture – this paper contributes an ethnography of collectors and collections of death, the dead and murder. It explores the idea that the cultural consumption of crime and death is driven by a desire for visceral, gruesome and violent experiences – and proposes that these desires are accessed, in the case of material objects, through consumptive values of antique, aura and authenticity.